Expression liabilities in a four‐chain bispecific molecule. Issue 10 (15th June 2021) - Guo, Cai; Chen, Fuyi; Xiao, Qiang; Catterall, Hannah B.; Robinson, John H.; Wang, Zhulun; Mock, Marissa; Hubert, René
Abstract: Multispecific antibodies, often composed of three to five polypeptide chains, have become increasingly relevant in the development of biotherapeutics. These molecules have mechanisms of action that include redirecting T cells to tumors and blocking multiple pathogenic mediators simultaneously. One of the major challenges for asymmetric multispecific antibodies is generating a high proportion of the correctly paired antibody during production. To understand the causes and effects of chain mispairing impurities in a difficult to express multispecific hetero‐IgG, we investigated consequences of individual and pairwise chain expression in mammalian transient expression hosts. We found that one of the two light chains (LC) was not secretion competent when transfected individually or cotransfected with the noncognate heavy chain (HC). Overexpression of this secretion impaired LC reduced cell growth while inducing endoplasmic reticulum stress and CCAAT/enhancer‐binding protein homologous protein (CHOP) expression. The majority of this LC was observed as monomer with incomplete intrachain disulfide bonds when expressed individually. Russell bodies (RB) were induced when this LC was co‐expressed with the cognate HC. Moreover, one HC paired promiscuously with noncognate LC. These results identify the causes for the low product quality observed from stable cell lines expressing this heteroIgG and suggest mitigation strategies to improve overall process productivity of the correctly paired multispecific antibody. The approach described here provides a general strategy for identifying the molecular and cellular liabilities associated with difficult to express multispecific antibodies. Abstract : Manufacturing of asymmetric multispecific antibodies is often challenging with low yield of correctly paired antibodies. Guo and coworkers developed an approach using transient expression systems and identified the causes for the low product quality observed from stable cell lines expressing the four‐chain bispecific HeteroIgG‐A. Mitigation strategies were proposed to improve overall process productivity of the correctly paired HeteroIgG‐A.